The Impact of Digital Marketing on Traditional Market Clothing Traders (Case Study of The Inpres Market in Palu City) - Dasa Febriyanti; Sri Haryani; Siti Zahwa (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to determine the impact of digital marketing on traditional clothing traders in Palu City and how traditional clothing traders respond to online traders. The type of research used was quantitative descriptive with a total of 150 clothing traders in traditional markets as respondents. Relationship variables were examined and analyzed using SPSS version 27 software. Based on the analysis results, it was found that there was a significant influence of digital marketing on traditional clothing market traders at the Inpres Market in Palu City.